Green Building Assessment and Recommendations for Optimization Case Study of the Rectorate Building the University of Lampung - Ika Kustiani; Masdar Helmi; Nur Syahidah Aini (Journal of Engineering and Scientific Research, 2023)
The Green Building Concept is a concept that offers a method of managing buildings with less energy and resources utilization to minimize the environmental impact. Since its implementation to be mandator, it is time for the University of Lampung to start implementing this concept. This research was aimed at assessing the Rectorate Building rating based on the national standard on Green Building Certification (Greenship-GBCI). There were several steps in conducting this research. Firstly, an opinion survey was conducted to measure the level of satisfaction of the building’s users. Secondly, a series of measurements related to lighting, temperature, humidity, noise, and air quality were carried out. Furthermore, an interview survey related to the operation and maintenance of the building were conducted. Finally, all of these data were entered in the Green Building rating tool for existing buildings. The results showed that the Rectorate Building score was 23 out of 117. This score is way below the score for a bronze rating of 35. Therefore, corrective action must be taken in order the building operation management to meet the Greenship-GBCI standard. Assessment also needs to be done on buildings througout the university for a reference in developing the University of Lampung Eco-campus program.